Penegakan Hukum terhadap Konten Promosi Judi Online yang Dilakukan oleh Influencer di Media Sosial - Kadek Oktavianiasih (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The development of information technology has facilitated access to various digital services, including online gambling. Online gambling is widely promoted by influencers on social media. This raises legal issues, considering that gambling is prohibited in Indonesia. Online gambling is often portrayed by influencers as an instant financial solution, enticing many people, especially the youth, who are easily influenced, to participate. The purpose of this study is to analyze the legislation related to the promotion of online gambling and assess the effectiveness of law enforcement related to such content on social media. The research method used is normative legal research, utilizing primary legal sources such as the ITE Law No. 11 of 2008, updated with Law No. 19 of 2016, and Article 303 of the Criminal Code. Law enforcement must be strengthened through cyber patrols, site blocking, and public education to raise awareness of the risks of online gambling. This study provides guidance for policymakers in designing preventive and repressive measures to combat the promotion of online gambling in Indonesia.